Enhancing rainfed safflower yield, oil content, and fatty acid composition through intercropping with chickpea and stress-modifier biostimulants - Mosalman, Salah; Rezaei-Chiyaneh, Esmaeil; Mahdavikia, Hassan; Dolatabadian, Aria; Siddique, Kadambot H.M. (Frontiers in Agronomy, 2024)
This study investigated the impact of stress modifiers in intercropping systems on seed yield and yield components, physiological traits, and antioxidant activity of safflower (Carthamus tinctorius L.) and chickpea (Cicer arietinum L.) under rainfed (water deficit) conditions. The experimental design included three stress modulator levels [control, 1 mM salicylic acid (SA), and 10 mM selenium (Se)] and five planting patterns [intercropping one row of safflower and two rows of chickpeas (1S:2C), two rows of safflower and four rows of chickpeas (2S:4C), and three rows of safflower and five rows of chickpeas (3S:5C), and sole cropping of safflower (Ss) and chickpea (Cs)]. The results revealed that Ss treated with Se produced the highest safflower biological yield (4,905.50 kg ha -1 ) and seed yield (1,259.50 kg ha -1 ), while Cs produced the highest chickpea biological yield (2,799.67 kg ha -1 ) and seed yield (852.44 kg ha -1 ), followed by Cs treated with SA (2,419.25 kg ha -1 and 764.83 kg ha -1 , respectively).Conversely, the 3S:5C intercropping ratio (IR) with Se application recorded the highest safflower oil content (32.08%), while Ss treated with Se produced the highest oil yield (358.62 kg ha -1 ). The 2S:4C configuration with Se application produced the highest unsaturated fatty acid (oleic and linoleic acids) concentrations in safflower, while 2S:4C and 3S:5C treated with Se produced the highest chlorophyll a and chlorophyll b contents in safflower and chickpea. Furthermore, 1S:2C and 2S:4C treated with SA or Se produced the highest proline and total soluble sugars in safflower and chickpea. The SA and Se treatments in the intercropping systems increased catalase, ascorbate peroxidase, and superoxide dismutase activities compared to the respective control plants (sole cropping) and enhanced oil contents, fatty acid 2 composition, physiological traits, and antioxidant properties. These results underscore the potential of intercropping systems coupled with stress modulator treatments as a sustainable approach for safflower and chickpea cultivation under rainfed conditions.